Human Sperm DNA Fragmentation and its Correlation with Conventional Semen Parameters - Evgeni, Evangelini (Avicenna Research Institute, 2014)
BACKGROUND: The initial step in the diagnostic investigation of male infertility has been traditionally based on the conventional seminal profile. However, there are significant limitations regarding its ability to determine the underlying mechanisms that cause the disorder. Sperm DNA fragmentation has emerged as a potential causative factor of reproductive failure and its assessment has been suggested as a useful adjunct to the laboratory methodology of male infertility evaluation, especially before the application of assisted reproduction technology (ART). METHODS: A review of recent bibliography was carried out in PubMed by the use of relevant keywords, in order to evaluate the possible correlation between the conventional seminal parameters and sperm DNA fragmentation assessment as diagnostic tools in male infertility evaluation. RESULTS: A comprehensive diagnostic approach of male infertility should be based on a combination of diagnostic attributes, derived from the conventional semen analysis, as well as the investigation of genomic integrity testing. CONCLUSION: Due to its strong correlation with several aspects of ART procedures and further consequences for the offspring, sperm DNA fragmentation is a parameter worth integrating in routine clinical practice. However, additional large scale studies focusing on specific subgroups of infertile men who may benefit from an efficient therapeutic management based on the optimization of sperm DNA integrity are needed.